Tyrosine phosphorylation of WASP promotes calpain-mediated podosome disassembly - Macpherson, Lee (Ferrata Storti Foundation, 2012)
Podosomes are actin-based adhesions involved in migration of cells that have to cross tissue boundaries such as myeloid cells. The Wiskott Aldrich Syndrome Protein regulates de novo actin polymerization during podosome formation and it is cleaved by the protease calpain during podosome disassembly. The mechanisms that may induce the Wiskott Aldrich Syndrome Protein cleavage by calpain remain undetermined. We now report that in myeloid cells, tyrosine phosphorylation of the Wiskott Aldrich Syndrome Protein-tyrosine291 (Human)/tyrosine293 (mouse) not only enhances Wiskott Aldrich Syndrome Protein-mediated actin polymerization but also promotes its calpain-dependent degradation during podosome disassembly. We also show that activation of the Wiskott Aldrich Syndrome Protein leading to podosome formation occurs independently of tyrosine phosphorylation in spleen-derived dendritic cells. We conclude that tyrosine phosphorylation of the Wiskott Aldrich Syndrome Protein integrates dynamics of actin and cell adhesion proteins during podosome disassembly required for mobilization of myeloid cells during the immune response.